Assessment of Outer Space Events on Troposphere and Climate Change over Iraq - Al-Awadi, Raghda S.; Al-Taai, Osama T.; Abdullah, Sundus A. (Iraqi Journal of Science, 2023)
The aim of the study is to investigate the effects of space weather on the troposphere, where our climate exists. This work is useful to give us an idea of ​​the interaction between solar activity and some meteorological parameters. The sunspot number (SSN) data were extracted from the World Data Center for the production, preservation, and dissemination of the international sunspot number (SILSO), top net solar radiation (TSR) and temperature 2 meters from the ERA5 model of the Copernicus Climate Change Service (C3S) from the Climate Data Store with 0.25 grid Resolution, providing a rich source of climate data for researchers. This study was conducted from 2008 to 2021 (solar cycle 24 and the beginning of 25) over Iraq located within latitude (38°N-28°S) and longitude (38°W- 49°E). The results that have been reached were a decrease in solar activity in solar cycle 24, accompanied by an increase in the length of the solar cycles, and there was a direct proportion between TSR and temperature. TSR and temperature had almost similar spatial distribution over Iraq. The northern regions received the least amounts, while from the middle toward the southeast regions, they received the highest amount of TSR and temperature over Iraq. There was a reverse regression between sunspot numbers with TSR and positive regression with temperature, but the correlation was not significant.